Boston Museum at 28 Tremont Street, ca. 1880-1900 - Unknown (Tufts Archival Research Center, 2005)
Elevated view south-southeast of the Boston Museum, located at 28 Tremont Street between Scollay Square to the northeast and School Street to the southwest. Signage and awnings adorn the facades of stores located on the first level of the museum building. The facade of the Boston Museum, which faces west-northwest, is adorned with street lights and wrought-iron railing. The King's Chapel Burying Ground is included in the upper-right side of the photograph. Horse-drawn vehicles fill Tremont Street. 7 1/8 x 9 1/2 Photographs